PENERAPAN NILAI-NILAI PANCASILA PADA PERILAKU KARAKTER GOTONG ROYONG SISWA KELAS IV DI SEKOLAH DASAR - Nur Salim; Eko Kuntarto; Alirmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the application of Pancasila values in shaping the cooperative character of fourth-grade students in elementary schools and the obstacles to applying Pancasila values in shaping the cooperative character of fourth-grade students in elementary schools. The approach used is qualitative with a case study method at SD Negeri 182/1 Hutan Lindung. Data collection was conducted through observation, interviews, and documentation. The results of the study indicate that, overall, the application of Pancasila values in efforts to shape students' cooperative character has been carried out by teachers through various learning activities related to the five principles. These activities include praying, modeling respectful behavior, commemorating national holidays, involving students in decision-making, and treating students fairly. In implementing Pancasila values, there are several obstacles that teachers face. Among them are challenges related to teachers' lack of understanding and insight into the meaning and implementation of the five principles, differences in students' socio-cultural backgrounds, insufficient understanding and modeling of national values within family and community environments, and limited class time for discussions, which can impact teachers' efforts to develop students' cooperative attitudes.